Effect of sialylation and complexity of FSH oligosaccharides on inhibin production by granulosa cells - Loreti, Rosana Nazareth (2013)
Granulosa cell inhibin A and B production is regulated by FSH and gonadal factors. This gonadotrophin is released as a mixture of glycoforms, which induce different biological responses in vivo and in vitro. Our aim was to determine the effect of recombinant human FSH glycosylation variants on inhibin A and B production by rat granulosa cells. Preparative isoelectrofocusing was used to isolate more acidic/sialylated (pH<4.00) and less acidic/sialylated (pH>5.00) rhFSH charge analogues. Concanavalin-A was used to isolate unbound and firmly bound rhFSH glycoforms on the basis of their oligosaccharide complexity. Granulosa cells, obtained from oestrogen-primed immature rats, were cultured with either native rhFSH or its glycosylation variants. Inhibin A and B were determined using specific ELISAs. Results were expressed as mean±SEM. Under basal conditions inhibin A was the predominant dimer produced (inhibin A: 673±55; inhibin B: 80±4 pg/mL). More acidic/sialylated charge analogues stimulated inhibin B production when compared to inhibin A at all doses studied; in contrast, less acidic/sialylated charge analogues stimulated inhibin A production and elicited no effect on inhibin B. Glycoforms bearing complex oligosaccharides showed a potent stimulatory effect on inhibin B when compared to inhibin A production (i.e. dose 1ng/mL: 4.9±0.5vs0.9±0.1 fold stimulation, P<0.001). Glycoforms bearing hybrid type oligosaccharides favoured inhibin A production (i.e. dose 4ng/mL 2.9±0.1vs1.6±0.1 fold stimulation, P<0.05). These results show that the sialylation degree as well as the complexity of oligosaccharides present in the rhFSH molecule may be considered additional factors that differentially regulate dimeric inhibin production by rat granulosa cells.